To volunteer or not to volunteer: the case of Malaysian public service retirees - Uttam Singh, Surjit Singh; Md. Sail, Rahim; Abu Samah, Bahaman; Tajudin Shah, Raja Ahmad; Lumayag, Linda Alfarero (Universiti Putra Malaysia Press, 2005)
There are thousands of retirees from the Premier and Managerial and Professional (PMP) group of the Malaysian Public Service who, after the mandatory retirement at the age of fifty-five or fifty-six, could contribute to the community gleaning from an improved longevity index for both male and female Malaysians in the recent years. This article attempted to decipher the difference between volunteer and non-volunteer retirees as far as the role of psychosocial and altruistic factors are concerned and what this difference would imply as far as motivating other retirees to engage in the voluntary work for the development of the Malaysian society. The psychosocial dimension includes the environment, lifestyle, personality and resources while altruism includes empathy, reciprocity and spirituality. Independent sample t-test was used to determine whether there was a significant difference for the psychosocial variables and altruism between the volunteers and non-volunteers. Findings of the study revealed that there was a significant difference between the volunteers and non-volunteers by looking at the effects of both psychosocial and altruism further indicating that these volunteers were more altruistic and whose psychosocial factors greatly influenced the volunteers' propensity to render voluntary service to the community.